'Gaps, mishaps and overlaps'. Nursing documentation: How does it affect care?. (December 2016) - Charalambous, Liz; Goldberg, Sarah
Complete, accurate and relevant nursing documentation is essential for the multidisciplinary comprehensive geriatric assessment (CGA) process which can improve older patients' outcomes following a hospital admission. Our aim is to understand older person nurses' experiences of and attitudes to documentation, via semi-structured, in-depth interviews of eight qualified nurses at an acute hospital trust. Interviews were analysed using the framework approach to identify key themes. Three overarching themes were identified: gaps, mishaps and overlaps. Gaps refer to information which was missing, inaccurate or inconsistent; mishaps refer to the consequences of these inaccuracies and inconsistencies; and overlaps refer to the problem of duplications in recording of information. Older person nurses report many inconsistencies, omissions and duplications in their documentation. This has implications for how nursing contributes to the CGA and the quality of care of older patients. New ways must be found to minimise and streamline existing documentation to ensure that records are complete, timely and person-centred. Nurses should be mindful that emerging digital technology systems do not create further problems. Ward nurses need to take greater control of development of documentation.